THE RELATIONSHIP BETWEEN LEARNING INDEPENDENCE, PARENTS ATTENTION AND UTILIZATION OF LEARNING RESOURCES WITH MATHEMATICS LEARNING OUTCOME - Anugrah Dewi Lestari; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Several factors can cause low student learning outcomes. Independence learning, parents' attention, and utilization of learning resources are possibly related to learning outcomes. This research aims to determine the presence or absence of a positive and significant the relationship between independent learning, parent's attention, and utilization of learning resource to Mathematics Learning Outcomes in Students Class VIII of State Junior High School (SMP Negeri) 3 Sumbang Purwokerto Central Java in Even Semester in Academic Year of 2018/2019. The population in this research was the students of VIII of SMP Negeri 3 Sumbang Purwokerto Central Java in the academic year of 2018/2019, consisted of class  VIII A, VIII B, VIII C, VIII D, VIII E, totaling 192 students. Class VIII A is a sample class that was taken with the random sampling technique. The writer uses the questionnaire method to collect independent learning data, parents' attention, and the utilization of a learning resource and test method to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between independence learning, parents' attention, and the utilization of learning resources with mathematics learning outcomes in students class VIII of SMP Negeri 3 Sumbang Purwokerto Central Java Even Semester Academic Year of 2018/2019. It is showed by Fcount  Ftable is   with and   with , with  ,  and , and , and .Several factors can cause low student learning outcomes. Independence learning, parents' attention, and utilization of learning resources are possibly related to learning outcomes. This research aims to determine the presence or absence of a positive and significant the relationship between independent learning, parent's attention, and utilization of learning resource to Mathematics Learning Outcomes in Students Class VIII of State Junior High School (SMP Negeri) 3 Sumbang Purwokerto Central Java in Even Semester in Academic Year of 2018/2019. The population in this research was the students of VIII of SMP Negeri 3 Sumbang Purwokerto Central Java in the academic year of 2018/2019, consisted of class  VIII A, VIII B, VIII C, VIII D, VIII E, totaling 192 students. Class VIII A is a sample class that was taken with the random sampling technique. The writer uses the questionnaire method to collect independent learning data, parents' attention, and the utilization of a learning resource and test method to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between independence learning, parents' attention, and the utilization of learning resources with mathematics learning outcomes in students class VIII of SMP Negeri 3 Sumbang Purwokerto Central Java Even Semester Academic Year of 2018/2019. It is showed by Fcount  Ftable is   with and   with , with  ,  and , and , and .